For the Gospel's sake : the rise of the Wycliffe Bible Translators and the Summer Institute of Linguistics - Aldridge, Boone, 1962- (Michigan : Grand Rapids : William B. Eerdmans Publishing company, 2018)
The two-sided mission organization comprising Wycliffe Bible Translators and the Summer Institute of Linguistics is a paradox that begs for an explanation. The Summer Institute has long been doing laudable linguistic, humanitarian work in many countries, while Wycliffe has been one of the largest, fastest growing, and most controversial Christian missionary enterprises in the world. In this wide-ranging study Boone Aldridge--a religious historian and twenty-year insider at WBT-SIL--looks back at the organization's early years, from its inception in the 1930s to the death of its visionary founder, William Cameron Townsend, in 1982. He situates the iconic institution within the evolving landscape of mid-twentieth-century evangelicalism, examines its complex and occasionally confusing policies, and investigates the factors that led, despite persistent criticism from many sides, to its remarkable rise to prominence
Includes bibliographical references and index
Keywords: Wycliffe Bible Translators -- History; Summer Institute of Linguistics -- History; Bible -- Translating -- History